THE REGULATION OF DEAMINATION OF ADENINE COMPOUNDS IN BREAST AND LIVER IN DMBA-INDUCED BREAST CANCER RATS TREATED BY HYPERICUM ALPESTRE (Proceedings of the YSU B: Chemical and Biological Sciences, 2024)
Cancer treatment is an ongoing struggle around the world, and research into its treatment and prevention is constantly deepening. Unrestricted cell proliferation is a hallmark of cancer. In cell reproduction, the exchange of purine nucleotides is of great importance, because they are involved in the synthesis of DNA, which is necessary for the uninterrupted process of cell division. The activities of deamination enzymes of purine nucleotides, nucleosides, and nitrogenous bases are altered during cancer development both in tumor tissue and in other tissues and organs of diseased animals. From this point of view, it is of great interest to study the changes in the activity of purine metabolism, the first stage of which is deamination. The aim of this work was the study the deamination alterations of AMP, ADP, ATP, as well as adenine and adenosine in the liver and breast tissue homogenates in rats with 7,12-DMBA-induced breast cancer. In the experimental model of rats, mammary cancer was induced by 7,12-DMBA, and further treatment was carried out with the Hypericum alpestre. In addition, we also observed the combined effect of H. alpestre extract and chemical inhibitors on the deamination of purine compounds. Data show a significant elevation of the adenine compounds' deamination level in the breast cancer group treated with H. alpestre extract compared with rats with DMBA-induced breast cancer. During the development of breast cancer in rats, a significant reduction in deamination levels was observed in the liver homogenate. This reduction was compared with the group treated with H. alpestre, where deamination levels showed a notable increase. The levels of deamination of adenine compounds after the treatment with H. alpestre herb become very close to the values typical of the samples of healthy animals. Thus, in conclusion, the mentioned herb's anticancer activity can be expressed by the elevation of the deamination levels of adenine compounds, and one of the molecular mechanisms of the anticancer effect can be the dysregulation of deamination of adenine compounds under the influence of the selected plant․
Keywords: deamination; purine; adenine compounds; herbal extract; DMBA-induced cancer